Successful transmission probability analysis for satellite-terrestrial integrated networks based on stochastic geometry - SONG Zixu; SUN Yaohua; LI Ruiwen; PENG Mugen (Dianxin kexue)
Satellite-terrestrial integrated network can effectively complement the coverage of terrestrial cellular networks, meeting the full-time, full-area communication requirements of the 6G.To thoroughly analyze the downlink successful transmission probability in satellite-terrestrial integrated networks, stochastic geometry tools were employed, where binomial point processes (BPP) and Poisson point processes (PPP) were adopted to model the spatial distributions of satellites and terrestrial base stations (BSs). A closed-form expression for the downlink successful transmission probability of a typical user was derived. The accuracy of the theoretical derivation was verified through Monte Carlo simulations, and the impacts of key network parameters—including the deployment void radius of terrestrial BSs, the number of orthogonal frequency channels in spatial links, and BSs density—on the downlink successful transmission probability were investigated under satellite-terrestrial heterogeneous frequency networking. The results indicated that: the satellite-terrestrial integrated network effectively addressed the deployment void problem of terrestrial BSs; within a certain range, increasing the number of satellite frequency-domain channel partitions or terrestrial BSs density significantly improved the downlink successful transmission probability.